2008
DOI: 10.3354/meps07678
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of three dominant myctophid species in the northern California Current region

Abstract: The feeding ecology of 3 dominant sympatric myctophid species (Tarletonbeania crenularis, Diaphus theta, and Stenobrachius leucopsarus) in the northern California Current System was investigated based on samples collected in June, August, and September of 2006. All 3 species fed predominantly on Euphausia pacifica, the most abundant euphausiid off the central Oregon coast. In contrast, the same 3 lanternfishes showed marked variation in utilization of other principal food categories, and stronger resource part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 46 publications
3
18
1
Order By: Relevance
“…Segregation is likely to operate through a combination of different factors, including morphological, physiological, and behavioral adaptations. Trophic ecology of myctophids was recently related to two ecomorphological types, the so-called active and inactive species, with the former being diel vertical migrants that store lipids as triacylglycerols and the latter being nonmigratory and partly migratory species containing wax esters (see details in Suntsov and Brodeur 2008). Such a classification is not supported by myctophids from Kerguelen since most species are active migrants (Duhamel et al , 2005, which, depending on species, store either triacylglycerols or wax esters (Phleger et al 1999;Lea et al 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Segregation is likely to operate through a combination of different factors, including morphological, physiological, and behavioral adaptations. Trophic ecology of myctophids was recently related to two ecomorphological types, the so-called active and inactive species, with the former being diel vertical migrants that store lipids as triacylglycerols and the latter being nonmigratory and partly migratory species containing wax esters (see details in Suntsov and Brodeur 2008). Such a classification is not supported by myctophids from Kerguelen since most species are active migrants (Duhamel et al , 2005, which, depending on species, store either triacylglycerols or wax esters (Phleger et al 1999;Lea et al 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Near Oregon, T. crenularis prey mainly on euphausiids, amphipods, and salps, and the largest specimens also consume bathylagid fish (Collard 1970;Hart 1973;Tyler and Pearcy 1975;Brodeur and Yamamura 2005;Suntsov and Brodeur 2008). In turn, T. crenularis constitutes an important prey item for many predators in the North Pacific, including jumbo squid (Field et al 2007;Zeidberg and Robison 2007), salmon, Sockeye salmon, albacore, Pacific hake, and sablefish (Rogachev et al 2000;Hart 1973, Davies et al 1988Buckley et al 1999;Nomura and Davis 2005), and Dall's porpoises (Ohizumi et al 2003).…”
mentioning
confidence: 99%
“…Mar Ecol Prog Ser 390: [277][278][279][280][281][282][283][284][285][286][287][288][289] 2009 Tanasichuk 2002, Brinton & Townsend 2003, Croll et al 2005, Suntsov & Brodeur 2008. Research has shown that the population biology of both of these euphausiids is influenced by ocean climate (Tanasichuk 1998a,b, Marinovic et al 2002, Brinton & Townsend 2003, Dorman et al 2005), but in a complex manner that remains poorly understood (Abraham & Sydeman 2004).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Across the California Current System (CCS), for example, the euphausiids Euphausia pacifica and Thysanoessa spinifera are important prey for many vertebrate predators (Brodeur & Pearcy 1992, Ainley et al 1996, Tanasichuk 2002, Brinton & Townsend 2003, Croll et al 2005, Suntsov & Brodeur 2008. Research has shown that the population biology of both of these euphausiids is influenced by ocean climate (Tanasichuk 1998a,b, Marinovic et al 2002, Brinton & Townsend 2003, Dorman et al 2005), but in a complex manner that remains poorly understood (Abraham & Sydeman 2004).…”
Section: Introductionmentioning
confidence: 99%